2003
DOI: 10.1021/la0344682
|View full text |Cite
|
Sign up to set email alerts
|

Wetting on Hydrophobic Rough Surfaces:  To Be Heterogeneous or Not To Be?

Abstract: Equilibrium wetting on rough surfaces is discussed in terms of the “competition” between complete liquid penetration into the roughness grooves and entrapment of air bubbles inside the grooves underneath the liquid. The former is the homogeneous wetting regime, usually described by the Wenzel equation. The latter is the heterogeneous wetting regime that is described by the Cassie−Baxter equation. Understanding this “competition” is essential for the design of ultrahydrophobic surfaces. The present discussion p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
1,045
4
10

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 1,329 publications
(1,078 citation statements)
references
References 30 publications
19
1,045
4
10
Order By: Relevance
“…[ 42,43 ] In the Wenzel state, a liquid droplet enters all the surface asperities. [ [43][44][45] In the Cassie-Baxter state, a liquid droplet is only in contact with the top of the surface roughness and also on air fractions trapped between the liquid droplet and the substrate. The Cassie-Baxter can predict superhydrophobic properties with low H water if the air fraction is suffi ciently important.…”
Section: Discussionmentioning
confidence: 99%
“…[ 42,43 ] In the Wenzel state, a liquid droplet enters all the surface asperities. [ [43][44][45] In the Cassie-Baxter state, a liquid droplet is only in contact with the top of the surface roughness and also on air fractions trapped between the liquid droplet and the substrate. The Cassie-Baxter can predict superhydrophobic properties with low H water if the air fraction is suffi ciently important.…”
Section: Discussionmentioning
confidence: 99%
“…between the liquid and the textured substrate becomes equal to the equilibrium contact angle " (given by Young's relation [22] ) for the three phase contact line. [23][24][25] The existence of points on the surface that enables the condition ! = " [26] to be fulfilled is a necessary, though not sufficient condition, [19,24,25,27,28] for the formation of a composite interface, such as the one shown in Fig.…”
mentioning
confidence: 99%
“…Existing approaches at surface design involve b/a ratio less than the critical limit 12,17,19,21,39,40 Although the critical limit is wellknown, the domains of dependent parameters, namely c/a ratio and θY have not yet been investigated. It can be shown that the critical limit assumes a positive real value, if and only if the Young's contact angle exceeds 90° (equation 8).…”
Section: Robustness With An Energetically Favorable Cassie State (Casmentioning
confidence: 99%